D-Shaped Photonic Crystal Fiber Toxic Metal Ions (Arsenic) Sensor Based on Surface Plasmon Resonance - Mohammed Jassam, Ghufran; Salman Ahmed, Soudad (Iraqi Journal of Physics, 2023)
In this work, a Photonic Crystal Fiber (PCF) sensor based on the Surface Plasmon Resonance (SPR) technology was proposed. A thin layer of gold (Au) was deposited on a D-shaped Photonic Crystal Fiber (PCF), which was coated with plasmonic chemically stable gold material with a thickness of 40nm. The performance parameters like sensitivity including wavelength sensitivity and amplitude sensitivity and resolution were evaluated by simulation using COMSOL software. The proposed sensor was created by using the finite element approach, it is numerically examined. The results show that the surface of D-shaped Photonic Crystal Fiber coated with Au behaves as a sensor to detect the refractive index (IR) of toxic metal ions. The impacts of the structural characteristics on the resonant spectra are also researched in order to improve sensing performance. The greatest amplitude sensitivity was 99.2 RIU-1 and maximum resolution was 4 x 10-5 RIU achieved within the detection range (1.351-1.363).